Józefa Życińskiego koncepcja pola racjonalności - Pabjan, Tadeusz (Filozofia Nauki, 2011)
One of the most important and the most valuable theme that can be found in the philosophical writings of Joseph Życiński is the idea of the field of rationality, which is a kind of a formal field constituted by a net of mathematical structures and abstract relations. This hypothesis explains the so called mathematicity and rationality of nature by assuming that formal structures are ontologically prior to the physical phenomena. In the present paper the idea of the field of rationality will be discussed. The article consists of three parts. The first deals with the problem of mathematicity which is a starting point of Życiński’s analyses, the second presents the most important features of the field he talks about, the third compares his idea with some concepts of Whitehead whose philosophy was his main source of inspiration.